2006
DOI: 10.1037/1072-5245.13.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fairness, leadership, and coping on strain, burnout, and turnover in organizational change.

Abstract: Procedural justice, supervisory style, and personal coping measures were obtained from 103 workers from two units of a nationwide engineering firm during and six months after a time-limited, company-wide computer system change. The two units employed significantly differing procedural justice approaches. Lower procedural justice was predictive of higher burnout, strain, and turnover. The patterns of relationship were somewhat different for burnout and strain, implying that these two affective responses to chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 46 publications
6
46
0
Order By: Relevance
“…Lower Preventive coping was related to Depersonalization; while higher problem focused coping was related to Personal Accomplishment. Related research indicates that Escape coping is also related to higher levels of Emotional Exhaustion and Depersonalization (Koeske, Kirk, & Koeske, 1993;Riolli & Savicki, 2006).…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lower Preventive coping was related to Depersonalization; while higher problem focused coping was related to Personal Accomplishment. Related research indicates that Escape coping is also related to higher levels of Emotional Exhaustion and Depersonalization (Koeske, Kirk, & Koeske, 1993;Riolli & Savicki, 2006).…”
Section: Meta-analysismentioning
confidence: 99%
“…Mirvis and Kanter (1989) identify that employment content such as working conditions, work groups and pay practices, is the best predictor of work attitudes and subject of praise or criticism. It is suggested that organizations must address this increasing cynicism by managing more fairly, and operating in an open, honest, straightforward, and particularly, realistic manner (Mirvis & Kanter 1989;Riolli & Savicki, 2006). Employees can participate in governance, provide regular reality checks to management, have positive role models, and perceive an open and honest pay system.…”
Section: Implications For Prevention and Interventionmentioning
confidence: 99%
“…Cropanzano, Rupp, and Byrbem (2003) conducted a study of hospital employees and found that emotional exhaustion accounted for intent to leave beyond the effects of age, gender and ethnicity. Roolli and Savicki (2006) found that higher levels of strain on the job predicted turnover above and beyond any contribution of procedural justice.…”
Section: Research On Intent To Leavementioning
confidence: 96%
“…Riolli and Savicki (2006) explore how supervision, among other things, influences the practitioner experiencing stressful events: organizational change, for instance, that happens in every human service organization, and how that change correlates with burnout.…”
Section: Impacts On Internal Clientsmentioning
confidence: 99%
“…Fifth, as all social workers practising in an agency are internal clients to that agency, it is important to understand the impacts that administrative and educative supervision can have on us, through the change process that happens regularly in the agencies we work in. Riolli and Savicki (2006) Collins-Camargo, 2007). If an organization is carrying out a change process it would benefit from having a strong culture of educative supervision in place, before the change process occurred.…”
Section: Finding Balance As An Administrator and Clinicianmentioning
confidence: 99%